Building Resilience: An Intervention to Enrich Positive Outcome in Personality Traits amongst Students - Wangchuk, Dorji (International Journal of Humanities and Education Development (IJHED), 2021)
The universal call for education in the 21st century gears towards cultivating personal traits of students who are resilient in navigating through life successfully. Thus, resilience building must be initiated in the learning institutions across the country for a better world. Resilience building enriches the personality traits and creates a wholesome individual who can in turn create a better world to be in. This study explored the impact of resilience building on academic performance and development of the personality traits in the young minds of Khasdrapchu MSS, Thimphu, based on five factor model of personality.The sample students were selected using need assessment and screening tools. The vulnerable students were prioritized to be intervened with resilience building program. 37 students from classes VII to X were selected employing purposive sampling technique. The methodology incorporated was quantitative approach. The research design chosen was pretest and post-test.In addition to a structured, self-administered questionnaire, the mid-term and annual examination results were included. Descriptive analysis was carried out to describe and summarize the raw data. Statistical techniques such as mean and standard deviation were used to infer correlation amongst the variables in the study.The inferential statistics results indicated that there was a positive correlation between resilience building and personality traits. This was supported by an increase in mean and standard deviation in the posttest after the intervention was provided. The academic performance of the students heightened after the intervention. It can be concluded that building resilience in students have positive outcomes on their personality traits and as well on their academic performance. Thus, the learning institutions must consider resilience building programs as interventions to help young people navigate through life well.